Students’ perception of online learning during the COVID-19 pandemic: A survey study of Polish medical students - Bączek, Michał; Zagańczyk-Bączek, Michalina; Szpringer, Monika; Jaroszyński, Andrzej; Wożakowska-Kapłon, Beata (Medicine (Baltimore), 2021)
The COVID-19 pandemic has disrupted teaching in a variety of institutions, especially in medical schools. Electronic learning (e-learning) became the core method of teaching the curriculum during the pandemic. After 8 weeks of only online learning, a survey was conducted to investigate perception of this type of learning among medical students.A survey was conducted by distributing an online questionnaire to Polish medical students. Data gathered from the survey were analyzed with routine statistical software.Eight hundred four students answered the questionnaire. According to respondents' answers, the main advantages of online learning were the ability to stay at home (69%), continuous access to online materials (69%), learning at your own pace (64%), and comfortable surroundings (54%). The majority of respondents chose lack of interactions with patients (70%) and technical problems with IT equipment (54%) as the main disadvantages. There was no statistical difference between face-to-face and online learning in terms of opinions on the ability of the learning method to increase knowledge (P = .46). E-learning was considered less effective than face-to-face learning in terms of increasing skills (P < .001) and social competences (P < .001). Students assessed that they were less active during online classes compared to traditional classes (P < .001). E-learning was rated as enjoyable by 73% of respondents.E-learning is a powerful tool for teaching medical students. However, successful implementation of online learning into the curriculum requires a well thought-out strategy and a more active approach.